Control Charts for Process Dispersion Parameter under Contaminated Normal Environments. (28th December 2015) - Ali, Amjid; Mahmood, Tahir; Nazir, Hafiz Zafar; Sana, Iram; Akhtar, Noureen; Qamar, Sadia; Iqbal, Muhammad
Abstract : Control charts are important statistical tool used to monitor fluctuations in the process location and dispersion parameters. The issues relating to the appropriate choice of control charts for the effective detection of process variability are addressed, and different control chart structures, such as Shewhart‐type, exponentially weighted moving average and cumulative sum are explored under ideal assumption of normality and contaminated normal environments, and hence, those control charts structures are identified which are more capable to detect aberrant changes in the process dispersion. Copyright © 2015 John Wiley & Sons, Ltd.